Numeracy skills students profile of Riau Province: content and construct instrument-based Riau culture and evaluation results - Andrian, Dedek; Nofriyandi, Nofriyandi; Wahyuni, Reni; Loska, Febri; Nurhalimah, Siti; Amir MZ, Zubaidah; Risnawati, Risnawati; Maisaroh, Siti; Dacara, Editha; Hidayat, Riyan (Institute of Advanced Engineering and Science, 2025)
Numeracy is an important ability of students and a foundation for future success. This research aimed to develop instruments, evaluate, and compare students’ numeracy skills of 12 regencies of Riau Province, Indonesia. The research population was every junior high school student in Riau Province with 260,787 students. The research sample is made up of some students who were taken by multiple random sampling of 1,193 students. The data collection technique of this research was the survey approach, with the main instrument being a multiple-choice test. Eight analysis data were used in this research: content validity, Cronbach alpha reliability, confirmatory factor analysis (CFA), reliability construct, descriptive, and one-way ANOVA. The content validity analysis showed that 4 items have to be revised because of the ambiguous sentences. Cronbach alpha reliability was acquired at 0.872 with the accepted category. CFA analysis showed 19 indicators as constructs were valid categories. Overall, the numeracy skills of 12 regency students of Riau Province were not a good category. One-way ANOVA analysis showed there was a significant difference in students’ numeracy skills between 12 districts in Riau Province, with a significant value of 0.000.